The role of recombinant LH in ovarian stimulation: what’s new? - Carlo Alviggi; Luigi Vigilante; Federica Cariati; Alessandro Conforti; Peter Humaidan (Reproductive Biology and Endocrinology)
Abstract It is widely recognized that luteinizing hormone (LH) activity is pivotal during folliculogenesis. Nonetheless, the use of LH during ovarian stimulation remains a matter of debate. Indeed, women with good LH function are able to sustain follicle growth and maturation during ovarian stimulation carried out with regimens based on follicle-stimulating hormone (FSH) alone. However, evidence exists that LH activity could be necessary in specific infertile subgroups undergoing assisted reproduction treatment (ART) who are characterized by a functional or constitutive LH deficiency. For instance, women with reduced sensitivity to gonadotropins, also called hypo-responders, usually present with a genetic condition that could impair the function of LH. Furthermore, women of advanced reproductive age present a less functional LH system and consequently reduced androgen production. Reduced ovarian sensitivity and advanced reproductive age represent the main criteria proposed by the POSEIDON group to identify women with impaired prognosis when undergoing ART. Hypogonadotropic hypogonadal women are characterized by undetectable LH levels, thus the addition of LH activity during stimulation is mandatory to achieve satisfactory follicular recruitment. The aim of the present review is to describe the role of recombinant LH in ovarian stimulation, identifying the specific infertile population for whom LH supplementation could improve the outcome of ART.